2013
DOI: 10.1002/mc.22008
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of fish oils against human lung cancer is associated with changes in formation of PGE2 and PGE3 and alteration of Akt phosphorylation

Abstract: The beneficial effects of omega-3 fatty acids are believed to be due in part to selective alteration of arachidonate metabolism that involves cyclooxygenase (COX) enzymes. Here we investigated the effect of eicosapentaenoic acid (EPA) on the proliferation of human non-small cell lung cancer A549 (COX-2 over-expressing) and H1299 (COX-2 null) as well as their xenograft models. While EPA inhibited 50% of proliferation of A549 cells at 6.05 μM, almost 80 μM of EPA was needed to reach similar levels of inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 47 publications
(63 reference statements)
2
42
0
1
Order By: Relevance
“…In addition, when COX-2 expression was reduced by siRNA or shRNA in A549 cells, the antiproliferative activity of EPA was also reduced. These results suggest that the ability of EPA to generate PGE3 through the COX-2 enzyme might be critical for EPA-mediated of lung cancer cells via down-regulation of Akt phosphorylation by PGE3 [170].…”
Section: Lung Cancermentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, when COX-2 expression was reduced by siRNA or shRNA in A549 cells, the antiproliferative activity of EPA was also reduced. These results suggest that the ability of EPA to generate PGE3 through the COX-2 enzyme might be critical for EPA-mediated of lung cancer cells via down-regulation of Akt phosphorylation by PGE3 [170].…”
Section: Lung Cancermentioning
confidence: 80%
“…A recent work suggested that this antiproliferative effect can be due in part to selective alteration of arachidonate metabolism that involves COX enzymes. EPA inhibited 50 % of proliferation of A549 cells (COX-2 over-expressing) at 6.05 μM, while almost 80 μM was needed to reach similar levels of inhibition of H1299 cells (COX-2 null) [170]. Accordingly, the formation of prostaglandin (PG)E3 in A549 cells was almost 3-fold higher than that of H1299 cells when they were treated with EPA (25 μM).…”
Section: Lung Cancermentioning
confidence: 97%
“…For some other types of cancer cells, Kim et al 42 studied the effect of DHA standard (10-60 µM) on the growth of lung cancer cells H1299 and A549; a dose-dependent decrease in cell viability was observed with the IC 50 being 46 and 40 µM, respectively. Similarly, the IC 50 was 50 and 9.7 µM, respectively, after the treatment of lung cancer cells H1299 and A549 with DHA standard (1-100 µM) 43 and was 162.5 µM for liver cancer cells MHCC97L when treated with DHA standard (0-200 µM). 44 For breast cancer cells MCF-7, MDA-MB-231, and MDA-MB-435, the IC 50 were 20.2, 57.4, and 70 µM, respectively, when treated with DHA.…”
Section: Cell Viability Of B16-f10 and Ccd986sk Cellsmentioning
confidence: 92%
“…Similarly, Xia et al and Hawcroft et al reported that the formation of PGE 3 in EPA treated mouse melanoma and human HCA-7 CRC cells was blocked by indomethacin [79] or a selective COX-2 inhibitor, SC-236, respectively [24]. The important role of COX-2 in regulating PGE 3 metabolism was further supported by the finding that a substantially lower amount of PGE 3 was detected in the H1299 cells (COX-2 null NSCLC cells) and its xenograft tumor tissues compared to that in A549 cells (COX-2 constitutively expressed) and its xenograft [80]. The formation of PGE 3 was partially blocked in the COX-2 knockdown A549 cells compared with the control siRNA administrated A549 cells.…”
Section: Cpla2 Cox-2 and Pge3 Metabolism In Cancermentioning
confidence: 99%